Electromyography in the diagnosis of radiculopathies - A. A. Rogozhin; F. I. Devlikamova (Нервно-мышечные болезни, 2015)
The paper considers techniques for the neurophysiological diagnosis of radiculopathies, such as needle electromyography, motor and sensor nerve, F-waves, and H-reflex studies. Data on the sensitivity of the used methods are presented. Recommendations for neurophysiologists are given with regard to the specific features of different methods and the interpretation of results.